The Role of the Film "Kejarlah Janji" as a Political Education Media for Senior High School and Vocational High School Beginner Voters during Indonesia's 2024 Legislative Election - Kenmada Widjajanto; Atalia Praratya (Smart Society, 2026)
The large proportion of novice voters in Indonesia’s 2024 Legislative Election, combined with their limited understanding of electoral procedures and vulnerability to political misinformation, highlights the need for innovative political education strategies. This study aims to examine the role of the film “Kejarlah Janji” as a political education medium for senior high school and vocational high school students as novice voters. A quantitative survey approach was employed using purposive sampling involving 33 respondents who had watched the film and met the criteria of novice voters. Data were collected through closed-ended and open-ended questionnaires and analyzed using descriptive quantitative analysis. The findings indicate that although most respondents had previously been exposed to election-related information, gaps remained in procedural understanding and active electoral engagement. After watching the film, respondents reported stronger motivation to participate in elections, better understanding of leadership criteria, greater awareness of misinformation, and stronger endorsement of democratic values such as honesty, responsibility, and fairness. These findings suggest that “Kejarlah Janji” functions not only as an informational medium but also as a contextual and engaging form of political education for young voters. The study contributes to the literature by demonstrating the potential of film-based political education to support political literacy, critical awareness, and democratic value formation among novice voters.